2013
DOI: 10.1088/0004-637x/773/2/163
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities Driven by the Drift and Temperature Anisotropy of Alpha Particles in the Solar Wind

Abstract: We investigate the conditions under which parallel-propagating Alfvén/ion-cyclotron (A/IC) waves and fastmagnetosonic/whistler (FM/W) waves are driven unstable by the differential flow and temperature anisotropy of alpha particles in the solar wind. We focus on the limit in which w α 0.25v A , where w α is the parallel alphaparticle thermal speed and v A is the Alfvén speed. We derive analytic expressions for the instability thresholds of these waves, which show, e.g., how the minimum unstable alpha-particle b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 37 publications
(52 reference statements)
3
66
0
Order By: Relevance
“…The various waves analysed here also depend on other plasma parameters such as β j of all species, the number of species, relative drifts among them, and their temperature anisotropies (Marsch et al 1982b,a;Kasper et al 2002;Bale et al 2009;Maruca et al 2012;Verscharen et al 2013;Yoon 2017;Klein et al 2018). It would be useful to repeat our investigation in individual cases when using plasma models with parameters different from the representative values used in this study (Riquelme et al 2015(Riquelme et al , 2016(Riquelme et al , 2018.…”
Section: Discussionmentioning
confidence: 91%
“…The various waves analysed here also depend on other plasma parameters such as β j of all species, the number of species, relative drifts among them, and their temperature anisotropies (Marsch et al 1982b,a;Kasper et al 2002;Bale et al 2009;Maruca et al 2012;Verscharen et al 2013;Yoon 2017;Klein et al 2018). It would be useful to repeat our investigation in individual cases when using plasma models with parameters different from the representative values used in this study (Riquelme et al 2015(Riquelme et al , 2016(Riquelme et al , 2018.…”
Section: Discussionmentioning
confidence: 91%
“…For example, fluctuations in the relative drift speed between alpha particles and protons, as well as fluctuations in their temperature anisotropy, can lead to the excitation of beam instabilities at average drift speeds below the classical thresholds of these instabilities (see Verscharen et al 2013a) and thus to limits on the beam speed that are lower than predicted by linear theory. The development of this theory is beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 99%
“…These velocities are moderately super-Alfvénic (see, e.g., Quest & Shapiro 1996;Verscharen et al 2013a). For parallel velocities within this velocity interval, we can use Equation (41) to approximate Equation (36) as…”
mentioning
confidence: 99%
“…[8] Ion temperature anisotropies and differential velocities are constrained by kinetic instabilities. Signatures of temperature-anisotropy driven instabilities are clearly observed in the solar wind Hellinger et al, 2006;Matteini et al, 2007;Maruca et al, 2012], and signatures of instabilities driven by differential velocity between ion species [Daughton and Gary, 1998;Verscharen et al, 2013] are also observed [Marsch and Livi, 1987;Tu et al, 2004;Goldstein et al, 2000;Matteini et al, 2013].…”
Section: Introductionmentioning
confidence: 92%
“…Ion temperature anisotropies and differential velocities are constrained by kinetic instabilities. Signatures of temperature‒anisotropy driven instabilities are clearly observed in the solar wind [ Gary et al , ; Hellinger et al , ; Matteini et al , ; Maruca et al , ], and signatures of instabilities driven by differential velocity between ion species [ Daughton and Gary , ; Verscharen et al , ] are also observed [ Marsch and Livi , ; Tu et al , ; Goldstein et al , ; Matteini et al , ]. It is unclear what the relations between a magnetohydrodynamic turbulence and/or important wave activity and kinetic instabilities are (which are usually investigated in the approximation of homogeneous plasma and uniform magnetic field).…”
Section: Introductionmentioning
confidence: 99%